PENGGUNAAN BAHASA IBU (MOTHER TONGUE) DI SEKOLAH DASAR - Wahidah Azzahra; Nanda Wafa Nabila; Yuli Pratiwi; Rizki Ananda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mother tongue is the first language that individuals acquire naturally through interactions in the family and community environment. In the world of elementary education, this language has an important role as the main means of supporting cognitive, social, emotional development, and strengthening children's cultural values. This study aims to examine the contribution of mother tongue in improving students' understanding of subject matter, as well as its impact on language skills and interaction with Indonesian. With a literature study approach, this study examines various scientific references that discuss the role of mother tongue in elementary school environments. The results of the study indicate that the use of mother tongue in the learning process can improve students' understanding, create a more conducive learning atmosphere, and provide a strong foundation in the multilingual learning process. In addition, good mastery of the mother tongue also strengthens students' metalinguistic awareness which is very important in acquiring a second language. However, if its use is not balanced with the right strategy, the dominance of the mother tongue can lead to code mixing which has an impact on limited mastery of the Indonesian language. Therefore, strategic integration of the mother tongue in learning at the elementary school level is needed, in order to support academic achievement while preserving local cultural heritage. This study recommends the importance of educational policies that support the balanced use of mother tongues as part of a contextual and inclusive teaching approach.